Impact of the Concentration Ethylenediamine on Optical Properties of Carbon Dots from Jengkol Peel (Archinendron pauciflorum) - Prayugo, Aniza S.; Marpongahtun, Marpongahtun; Gea, Saharman (Jurnal Akademika Kimia, 2023)
Carbon dots (CDs) are a new member of fluorescent nano carbons that have attracted attention because of their potential applications derived from their optical, chemical, and electrical properties. CDs from jengkol peel via the solvothermal method at 200 oC for 7 h with the addition of ethylenediamine (EDA) as a heteroatom dopant have been successfully carried out. This study aims to determine the effect of concentration EDA on the optical properties of CDs for the possible reason. The results revealed that the CDs solution has fluorescence properties; that bluish-green glow can be observed under ultraviolet radiation (365 nm). The UV - Vis absorption peaks did not depend on the CDs concentration, but the absorbance intensity decreased with increasing EDA concentration. The best fluorescence properties were possessed by 10 % EDA in CDs which produced λex/λem of 370 nm/518 nm, respectively, with a quantum yield of 42 %. The FTIR spectra of all samples showed that the CDs surface had functional groups such as carboxylic acids, hydroxyl, and amines. The obtained CDs have the potential to be used as heavy metal ion detectors, bioimaging, and antibacterial agents.